2018
DOI: 10.3847/1538-4357/aaa0d9
|View full text |Cite
|
Sign up to set email alerts
|

Power-law Statistics of Driven Reconnection in the Magnetically Closed Corona

Abstract: Numerous observations have revealed that power-law distributions are ubiquitous in energetic solar processes. Hard X-rays, soft X-rays, extreme ultraviolet radiation, and radio waves all display powerlaw frequency distributions. Since magnetic reconnection is the driving mechanism for many energetic solar phenomena, it is likely that reconnection events themselves display such power-law distributions. In this work, we perform numerical simulations of the solar corona driven by simple convective motions at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 68 publications
2
33
0
Order By: Relevance
“…Its Flux Corrected Transport algorithms (DeVore 1991) provide minimal, though finite, numerical dissipation, which allows magnetic reconnection to occur. As a result, ARMS conserves the magnetic helicity in the system to an excellent approximation, even when reconnection occurs throughout a substantial fraction of the total volume (Knizhnik et al 2015;Knizhnik et al 2017a;Knizhnik et al 2017b;Knizhnik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Its Flux Corrected Transport algorithms (DeVore 1991) provide minimal, though finite, numerical dissipation, which allows magnetic reconnection to occur. As a result, ARMS conserves the magnetic helicity in the system to an excellent approximation, even when reconnection occurs throughout a substantial fraction of the total volume (Knizhnik et al 2015;Knizhnik et al 2017a;Knizhnik et al 2017b;Knizhnik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic spectral index of ∼0.5 must also be explained. An avalanche-like behavior of reconnection events is one possibility (Knizhnik et al, 2018). We must remember that, because of topological complexities such as separators and QSLs, the velocity pattern in the photosphere-which may be dominated by one scale-is translated into a different velocity pattern in corona, likely involving a range of scales.…”
Section: Discussionmentioning
confidence: 99%
“…see discussion in; Parnell & De Moortel 2012), and power law distributions of nanoflares can explain the observed range in differential emission measure slopes found in active regions (Cargill 2014). Many theoretical models have also suggested that nanoflares occur with a powerlaw distribution in energy, from a simple cellular automaton (López Fuentes & Klimchuk 2015) to full three dimensional magnetohydrodynamic (MHD) simulations (Knizhnik et al 2018). These models and observational considerations typically find nanoflare energy distributions with power laws of −2.5 α −1.5.…”
Section: Power Law Slopes Of Event Delaysmentioning
confidence: 99%